2020
DOI: 10.1186/s12882-020-02122-y
|View full text |Cite
|
Sign up to set email alerts
|

Significance of urinary fatty acid-binding protein 4 level as a possible biomarker for the identification of minimal change disease in patents with nephrotic-range proteinuria

Abstract: Background Fatty acid-binding protein 4 (FABP4), but not FABP1 (liver-type FABP), is ectopically induced in injured glomerular endothelial cells, and urinary FABP4 (U-FABP4) level is associated with proteinuria and renal dysfunction in a general population. Methods The clinical significance of U-FABP4 was investigated in 81 patients (male/female: 43/38, age: 57 ± 17 years) who underwent kidney biopsy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…and liver‐specific injury by DT‐R/DT system) (Figures 1B–D , 5C , and 6C ). Consistently, in patients with minimal change nephrotic syndrome or minor glomerular abnormalities, urinary FABP1 levels do not increase despite a marked increase in urinary albumin [ 28 , 29 ]. These observations reinforce our argument that a large amount of filtered FABP1 is efficiently reabsorbed in PTECs unless proximal tubular endocytosis is impaired (Figure 6E ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and liver‐specific injury by DT‐R/DT system) (Figures 1B–D , 5C , and 6C ). Consistently, in patients with minimal change nephrotic syndrome or minor glomerular abnormalities, urinary FABP1 levels do not increase despite a marked increase in urinary albumin [ 28 , 29 ]. These observations reinforce our argument that a large amount of filtered FABP1 is efficiently reabsorbed in PTECs unless proximal tubular endocytosis is impaired (Figure 6E ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that urinary FABP1 levels are concomitantly increased with markers of hepatic injury (aspartate aminotransferase, AST, and alanine aminotransferase, ALT) and hypoperfusion (lactate) but not serum creatinine in patients admitted to the intensive care unit [ 26 ]. Other studies have shown that urinary FABP1 levels do not increase in patients with liver dysfunction alone [ 27 ] or nephrotic syndrome with minimal glomerular abnormalities [ 28 , 29 ]. It has also been shown that an increase in urinary FABP1 levels is not associated with elevated serum FABP1 levels in patients with septic shock [ 30 ] or in those who have undergone cardiac surgery [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only a few proteins were found to be differentially secreted into the supernatants of infected cells, but striking differences were observed between the two viruses. Indeed, LASV induced the early release of MAST4, a serine/threonine kinase [ 71 ]; FABP1, a lipid chaperone [ 72 ]; and kallikrein (KLKB1). Tissue kallikrein, a serine protease, is known to be synthesized and released by human ECs, resulting in the generation of kinins, such as bradykinin [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, a study showed that microbiota from the intestines as well as the intestinal barrier integrity might affect the correlation between NAFLD and CKD through the gut-liver-kidney signaling axis [30]. Studies have shown that the dysregulation of adipokines in patients with MAFLD, including decreased adiponectin and increased fatty acid-binding protein 4 [31], may lead to renal dysfunction [32], glomerular injury [33], tubule-interstitial injury [34], and a decline of eGFR [35].…”
Section: Principal Findingsmentioning
confidence: 99%